PERKEMBANGAN PSIKOSOSIAL ANAK PADA KELUARGA BURUH MIGRAN INTERNASIONAL DI WILAYAH KABUPATEN KENDAL - Tri Nurhidayati; Desi Ariyana R; M. Fatkul Mubin (Universitas Muhammadiyah Semarang, 2014)
This study aims to identify psychosocial development of the children. It is based on several studies that families become overburdened with children entrusted, the child's relationship withher mother became strained, unruly children and school dropouts. Family is the first level ofsocial group, the first place for learning about values and the formation of the child's personality structure through the values and norms of the parents. Yet with his parents, especially mothers working abroad will have much effect on the child. Problems that are often experienced bychildren whose parents work abroad (especially mothers) migrated abroad to earn money for thefamily, many children who pass through the golden age without the guidance of a mother, even though this period determine the most critical period for children. Though the mother would not be replaced by anyone. Children who left a lot of experience psychosocial problems such asemotional disorders, behavioral problems, hyperactivity, tend to be more passive in terms ofaddressing issues that arise both families and schools. The study was conducted in the area ofKendal, precisely at Taman Gede village, Gemuh subdistrict. Taman Gede is one of the villagesin the district, which send many citizens working abroad according to one of the company'smost labor suppliers at Gemuh districts. Kendal selected based on the results BNP2TKI reportstating that Kendal area was ranked as the ninth highest labor suppliers in Indonesia in2012. Respondents are selected based on inclusion criteria that is international migrant worker'sfamily with family members (mother) who left children aged 0 -18 years. The research used descriptive method design to analyze and describe the psychosocial development of thechildren. Analysis using univariate analysis. The results of the study were obtained either psychosocial development of the child as many as 24 people (60%). Unfavorable psychosocia ldevelopment that have familiar friends play. have significant achievements in life. Keywords: Psychosocial, Children, Families of migrant workers